ObeM 2.0: Obesity management secured system 2.0 - Syifak Izhar, Hisham; Dayanandan@Anandan, Dinesh; Siti Zuhaidah, Shahadan; Nurlisa Fatihah, Abd Rani (2021)
Obesity issue is a critical issue at Malaysia. It leads to economic costs, direct & indirectly.